Water-retention properties of xanthan-gum-biopolymer-treated soils - Chang, Ilhan; Cho, Gye Chun; An Tran, Thi Phuong (Environmental Geotechnics, 2023)
This study aimed to estimate the effects of the xanthan gum biopolymer on the wetting and drying processes of soils. Xanthan gum with different contents by the mass of dried soil was used to treat Jumunjin sand and sand-clay mixtures. The wetting and drying soil-water characteristics of xanthan-gum-biopolymer-treated sand were investigated using capillary rise open tubes and a Fredlund-type soil-water characteristic curve device, respectively. The results show that xanthan gum has a significant effect on controlling the movement of water in soil. The xanthan gum biopolymer shapes the drying soil-water characteristics of soil, and there is a non-linear relationship between the xanthan gum content and the soil-water characteristic parameters of the treated soils. Xanthan gum significantly reduces the capillary conductivity of soil down to 10-7-10-8 m/s for soil treated with 1.0% xanthan gum. Xanthan gum affects the capillary equilibrium process of water differently in wetting tests as well. Furthermore, the wetting results show the role of clay particles in the flow-controlling performance of xanthan gum.
Keywords: Clay mixtures; Hydrophilics; Industry infrastructure; Industry innovations; Process of soil; Soil water characteristics; Treated soils; UN SDG 9: industry, innovation and infrastructure; Water retention properties; Wetting and drying process; biopolymer; environmental impact; hydrophilic; UN SDG 9: Industry, innovation and infrastructure; wetting